Prospects of use of computer system HUBER in rehabilitation, injury prevention and physical rehabilitation - Popadyuha Y.A; Korobeynikov G.V (Kharkov National Pedagogical University, 2012)
Features, efficiency and possibility of application of the modern computer systems are appraised in making healthy, prophylaxis of damages and physical rehabilitation. The prospects of the use of computer systems are considered for a design and correction of figure. The features of construction and action of the computer systems are resulted. It is marked that the innovation of technology consists in the principle new method of organization of procedure and in simultaneous influence on all locomotorium of man. The results of researches of the Russian specialists are resulted. Directions of increase of power and co-ordinating indexes are rotined. Attention on the features of structure and maintenance of health, aesthetically beautiful and therapeutic tasks is accented. Directions of the use of the computer systems are recommended in renewal of the state of organism of man after the considerable physical loadings.